ANALISIS HUBUNGAN ANTARA EFISIENSI KINERJA INTELEKTUAL TERHADAP KINERJA PERUSAHAAN STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Widaryanti . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2012)
The principal purpose of the present paper is to investigate the association between the efficiency of value added Intellectual Coefficient (VAIC) by the major components of a manufacture enterprise resource base {employee capital (CEE), human capital (HCE) and structural capital (SCE)} and ROA as dimension of manufacture enterprise financial performance. The traditional dimension of financial performance is profitability and market valuation. The study used 32 manufacture enterprises data drawn from Jakarta Stock Exchange (JSX) reporting period 2008-2010. The paper used two models to testing, the first between the Value Added Intellectual Coefficient (VAIC) as the efficiency measure of three intellectual capital components and financial performance. The second model explores the relation between every intellectual capital variables as independent variables and market valuation. The result is VAIC have relation with financial performance, but have’nt relation with market valuation.